Non-compliance of Malaysia motor vehicles (safety seatbelts) Rules 1978 - Sambasivam, Sivasankar; Karuppiah, Karmegam; Mohd Tamrin, Shamsul Bahri; Subramaniam, Kulanthayan; Sadeghi Naeini, Hassan (Tehran University of Medical Sciences, 2014)
Background: Seat belts have been proven as one of the most successful means of preventing or reducing injuries to occupants of cars during an accident. This paper examines the reasons behind the non-compliance of the seat belt law in Malaysia and suggests possible measures to get the percentage of seat belt usage up higher. Methods: Various databases of articles were searched for seat belt usage in Malaysia, related legislation, related accident data, type of injuries and reviewed to put forth the need for a new measure to increase the usage of seat belts in Malaysia. Results: In various studies carried out previously, car occupants (driver and front passenger) used the seat belts mainly with the knowledge that seat belts prevents injuries, the fear of being fined by the authorities, comfortability of the seat belt, speed of travel, trip purpose and driving location. However, when these factors are removed, seat belts usage starts becoming lax. Other reasons were driving short distance (known location), forgetfulness and were in a hurry. Conclusion: Enforcement of seat belt usage by either the Police or Road Transport Department is only a short term solution. The relevant agencies are urged to consider making compulsory for all car makers in Malaysia to enable a system where the car would not be able to start without the seat belt being fixed first for the driver and passenger and to make auto seat belt fixing enabled in the car when the driver and or passenger enters the car.